Chapter 10. Chipping Potato Variety Trial, 2006 - Chad M. Hutchinson; Doug Gergela (EDIS, 2007)
This is a multi-chapter report by C.M. Hutchinson and Doug Gergela. In the process of being published by the UF Department of Horticultural Sciences, January-July 2007.